2007
DOI: 10.1016/j.clim.2007.03.471
|View full text |Cite
|
Sign up to set email alerts
|

Immune Opsonins Modulate BLyS/BAFF Release in a Receptor-specific Fashion

Abstract: TNF ligand superfamily member 13B (B-lymphocyte stimulator (BLyS), B cell activating factor (BAFF)) promotes primary B cell proliferation and immunoglobulin production. While the soluble form of BLyS/BAFF is thought to be the primary biologically active form, little is known about the regulation of its cleavage and processing. We provide evidence that Fcγ receptor cross-linking triggers a rapid release of soluble, biologically active BLyS/BAFF from myeloid cells. Surprisingly, this function is primarily mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…These investigators reported that Fc γ receptor cross-linking by either CRP or IgG IC induced the release of BLyS/BAFF from myeloid cells [164]. They further found that CRP, like IC, induced release of BLyS through the high affinity receptor for IgG, Fc γ RI.…”
Section: Pentraxins In Autoimmune Diseasementioning
confidence: 99%
“…These investigators reported that Fc γ receptor cross-linking by either CRP or IgG IC induced the release of BLyS/BAFF from myeloid cells [164]. They further found that CRP, like IC, induced release of BLyS through the high affinity receptor for IgG, Fc γ RI.…”
Section: Pentraxins In Autoimmune Diseasementioning
confidence: 99%
“…If the transferred T cells produce TRAIL then it may bind to DR5 (a TRAIL receptor) on the surface of smooth muscle cells and cause their apoptotic death30. It appears accordingly that activated T cells, probably displaying adhesion molecules31, present in patients with SLE may enter vessels in which the resident DC have been activated and contribute significantly to the expression of vessel pathology in the form of atherosclerotic plaques. Macrophages may differentiate in the present of lupus serum to DC32 and may account for increased presence of DC in the vessel walls of SLE patients.…”
Section: Accelerated Atherosclerosis In Autoimmune Diseasesmentioning
confidence: 99%
“…For example, recent work has shown the unique ability of FcγRIa to facilitate antigen presentation. Even more surprising is our recent finding that FcγRIa is unique amongst FcγR, and amongst other γ-chain associated Fc receptors, in its ability to regulate the cell surface expression of TNFSF13b (also called BLyS or BAFF) upon cross-linking with either IgG ligand or with the innate immune opsonin CRP37. Other differences in receptor function are the result of differences in cell surface expression.…”
Section: Human Fcγ Receptor Structure and Functionmentioning
confidence: 99%